1972
DOI: 10.1002/1097-0142(197202)29:2<327::aid-cncr2820290210>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Pheochromocytoma

Abstract: Pheochromocytomas often develop in old, irradiated parabiotic NEDH rats. We have transplanted one for 2 years that is hormonally active. Subcutaneous transplants are successful in NEDH rats but do not take in the Sprague‐Dawley strain. Transplant‐bearing adolescent animals at first gained weight more rapidly than the controls, then lost weight and died within 30 to 60 days. Systolic blood pressure rose to an average of 167 mm Hg. Vanilmandelic acid and urinary metanephrines were sharply elevated, and there was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0
2

Year Published

1973
1973
1994
1994

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(35 citation statements)
references
References 4 publications
0
33
0
2
Order By: Relevance
“…The most definitive work on the purification of tyrosine 3-monooxygenase appears to be a recent report by Markey et al [3]. The purified the enzyme about 83-fold to a specific activity of 373 nmol min-' mg-' with a 9 % yield from PC-12 clonal cell lines, which were derived from a transplantable rat adrenal medullary pheochromocytoma [21,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most definitive work on the purification of tyrosine 3-monooxygenase appears to be a recent report by Markey et al [3]. The purified the enzyme about 83-fold to a specific activity of 373 nmol min-' mg-' with a 9 % yield from PC-12 clonal cell lines, which were derived from a transplantable rat adrenal medullary pheochromocytoma [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the activated state induced by purification was similar to that induced by phosphorylation through the action of CAMP-dependent protein kinase in their pH profiles for the enzyme activity and affinities for a pterin cofactor but was dissimilar in their V values, suggesting that both the activated states might result from distinct conformational alterations of the enzyme. The activation of the enzyme by the addition of polyanions [19], anionic phospholipids [20] and salts [21] was observed with partially purified enzymes from rat brains or bovine brains. In each case the stimulation appeared to be largely due to a decrease in the K , of the enzyme for its pterin cafactor.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that cocaine directly impairs neuronal differentiation and/or growth. As a model of in vitro neuronal differentiation, we used PC-12 cells, a clonal cell line derived from a transplantable rat adrenal pheochromocytoma induced by x-ray irradiation (18)(19)(20). These cells grow in culture as undifferentiated neuroblast cells that are exquisitely sensitive to the mitogenic effects of IGF-I.…”
Section: Introductionmentioning
confidence: 99%
“…Warren, DeLellis et al (4,5) have reported the induction and partial characterization of a transplantable rat pheochromocytoma which expressed the differentiated properties of adrenal chromaffin cells in vitro. Recently, we reported (6) that chromaffin granule-containing cells cultured from this tumor responded to treatment with nerve growth factor protein (NGF) (7)(8)(9) by extending long, branching neuronal-like processes.…”
mentioning
confidence: 99%